PENINGKATAN KETERAMPILAN MENULIS SURAT DENGAN PENDEKATAN CONTEKSTUAL TEACHING & LEARNING PADA SISWA KELAS IV - Juriah, Marta (Jurnal Visi Ilmu Pendidikan, 2018)
Abstract: This study aims to find out how much influence the contextual teaching and learning approach can improve the writing skills of letters grade IV students SDN 04 Nanga Pinoh. The type of research is Classroom Action Research designed by using cycle model by Kemmis and Mc Taggart. Where in the implementation of this PTK action consists of 4 stages, namely: planning, implementation of action, observation and reflection, with the aim to compare the value before the action and after the action. Technique of data collecting is done by observation observation and result of student learning test. The subjects of the study were the fourth grade students of SDN 04 Nanga Pinoh, which amounted to 27 people. There was an increase of learning achievement by using Contextual Teaching & Learning approach of personal letter writing writing to fourth grade students of SDN 04 Nanga Pinoh. This is evident in the increase in the value of the initial test of 27 students by 64 with 63% of students experiencing completeness. In cycle I the average value obtained by 80 then in cycle II the average value obtained increased by 81 with 92% of students experiencing completeness in learning. Based on these data it can be seen that the contextual teaching and learning approach can improve the writing skill of grade 4 students of SDN 04 Nanga Pinoh.Keywords: Contextual Teaching & Learning Approach, Writing SkillsÂ